Prematurity and low birthweight: Experience at the National Hospital Cayetano Heredia. - Trelles, Juan (2015)
Retrospective partial longitudinal comparative, observational study that evaluates 2155 newborns from a total of 18808 delivered between January 1984 and December 1987 at Cayetano Heredia National Hospital. Incidence of preterm newborns was 4,92% and of low birth weight 7,4%; 4,7%  were preterm low weight newborns. Risk of preterm low weight is influenced by demographic factors (parity, educational degrees), maternal past history (bad obstetrical history, prematurity, toxemia, and hypertension) and complications of current pregnancy. Important pregnancy associated medical complications were malnutrition, anemia and intercurrent infections. Preterm low weight newborns are associated to higher risk pregnancies, no prenatal control, severe neonatal hypoxia, and higher morbidity and mortality rates.